Pengembangan Konsep Desain Citra Kawasan Eduwisata Herbal di Kota Batu - Choirul Mahfud; Zainul Muhibbin; Niken Prasetyawati; Arman Hakim Nasution; Gogor Arif Handiwibowo; Hertiari Idajati; Ema Umilia; Edy Subali (LP3M STAI Darussalam Krempyang Nganjuk, 2021)
ABSTRACT The village community needs the development of alternative designs that are suitable for the Herbal Education area in Batu City for the progress of Indonesia. The activities' strategy is planning an alternative design concept for the Batu City Herbal Education Area. This community service has theoretical benefits that add insight and knowledge about determining educational tours' location with various approaches. In practical terms, several added values are useful for providing input to officials and policymakers for Batu City tourism development, specifically in developing tourism with the concept of education through city image theory. This activity's impact is a good effect of these activities, especially landmarks that function optimally in building the area's image for visitors/observers in the development of the herbal education area of Batu City. More than that, it can also provide an impression/experience to visitors/observers regarding the state of the Batu City herbal education area. Also, to support in comparing the herbal education area of Batu city.